2012
DOI: 10.1073/pnas.1203789109
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the p53 pathway by small-molecule-induced MDM2 and MDMX dimerization

Abstract: Activation of p53 tumor suppressor by antagonizing its negative regulator murine double minute (MDM)2 has been considered an attractive strategy for cancer therapy and several classes of p53-MDM2 binding inhibitors have been developed. However, these compounds do not inhibit the p53-MDMX interaction, and their effectiveness can be compromised in tumors overexpressing MDMX. Here, we identify small molecules that potently block p53 binding with both MDM2 and MDMX by inhibitor-driven homo-and/or heterodimerizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
211
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(224 citation statements)
references
References 39 publications
12
211
0
1
Order By: Relevance
“…The overall results of this study provide some interesting new insights into the molecular profile of WD/DD LPS that not only help to explain their variable sensitivity to Nutlin-3A in vitro and in the clinical setting, but also support the development of dual MDM2/MDMX compounds 38 that are expected to improve clinical outcomes in non-resectable WD/DD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall results of this study provide some interesting new insights into the molecular profile of WD/DD LPS that not only help to explain their variable sensitivity to Nutlin-3A in vitro and in the clinical setting, but also support the development of dual MDM2/MDMX compounds 38 that are expected to improve clinical outcomes in non-resectable WD/DD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The lower affinity of MDM2-B, which was further confirmed by MD simulations, is keeping with preclinical in vitro and in vivo data 37 and supports the idea that MDM2-B may contribute to the formation of cancer by means of a TP53-independent mechanism. 38 In particular, transduction of MDM2-B into a variety of cell types reveals that MDM2-B promotes TP53-independent cell growth, inhibits apoptosis, and upregulates the RelA subunit of NF k B. 38 and that is expected to correlate with a more aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the detailed mechanism of p53 inhibition by MDMX is still unclear, previous studies using p53-mimetic peptides and small molecule disruptors showed that MDMX-p53 binding is a critical step for p53 inactivation (18,19). MDMX-p53 binding is stimulated by CK1α, which is a major binding partner of MDMX.…”
Section: Discussionmentioning
confidence: 99%
“…However, to take full advantage of the strategy to stabilize p53 function, MDM2 and MDMX need to be targeted [86]. Such dual-activity inhibitors were identified by high-throughput screening by scientists at Roche and belonged to the class of indolyl-hydantoins [87]. Surprisingly, biochemical experiments and the co-crystal structure of MDMX or MDM2 in complex with one of these compounds, (5Z)-5-[(6-chloro-7-methyl-1H-indol-3-yl)methylidene]-3-(3,4-difluorobenzyl)imidazolidine-2,4-dione (RO2443; Table 1), revealed that RO2443 bound to the interface of the homodimers and stabilized their interaction.…”
Section: Ro2443mentioning
confidence: 99%